Expression analysis of notch signaling pathway molecules in SHED cultured in keratinocyte growth medium - Mohd Taha, Siti Aisyah; Koh Su Ling, Joanne; Azmi, Nur Izyan; Thirumulu Ponnuraj, Kannan; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah (Piracicaba Dental School, Brazil, 2015)
Aim: To detect the expression of molecules associated with Notch signaling pathway in stem cells from human exfoliated deciduous teeth (SHED) cultured in specific differentiation medium, namely, keratinocyte growth medium (KGM). Methods: RNA was extracted from SHED harvested on day 1, 3 and 7. RNA was reverse-transcribed to obtain the cDNA and then proceeded with PCR using specific primers for the Notch signaling pathway molecules (Notch1, Jagged-1, Jagged-2 and, Hes1) as well as stem cell marker (Nanog). PCR products were electrophoresed on a 2% agarose gel and stained with SYBR green. Results: Notch-1 was highly expressed in SHED cultured in KGM and showed increase in density as the days progressed, while Jagged-1 showed a decrease. Jagged-2 on the other hand, showed a slight increase on day 3 followed by a decrease on day 7. However, Hes-1 was not expressed in SHED cultured in KGM. Nanog showed expression only on day 3 and gradually increased in expression on day 7. Conclusions: Notch signaling pathway associated molecules; Notch-1, Jagged-1, Jagged-2, and stem cell marker Nanog are expressed in SHED cultured in KGM which may be involved in the differentiation into epithelial-like cells in human dental pulp tissues. Keywords: receptors, notch; gene expression; stem cells; tooth, deciduous; culture media.